If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8c + -12 = 36 Reorder the terms: -12 + -8c = 36 Solving -12 + -8c = 36 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -8c = 36 + 12 Combine like terms: -12 + 12 = 0 0 + -8c = 36 + 12 -8c = 36 + 12 Combine like terms: 36 + 12 = 48 -8c = 48 Divide each side by '-8'. c = -6 Simplifying c = -6
| 16(6)+24=-18+9(6) | | 3m+2=14 | | 3x+6=.78 | | 2(d-4)=-2 | | 4.3(x)=28.81 | | 7(x-5)=56 | | 9=12x-7 | | x^2-50=0 | | 13+12x=-6x+49 | | 2[2x-2]=12 | | 12.4+2a=5a+5.5 | | -6-5n=8 | | -5x=-2.5 | | -7(p-5)=-7(1+7p) | | -j+3j+2=32 | | 62=9y+5(y+4) | | 0.5(4x+8)=1.6-(x+2) | | -27+15(2.5)=33-9(2.5) | | 1.8*.3= | | 62=9y+5(y+5) | | -y-11=25 | | 1.8*3= | | 7*8x=3y | | 6w^2+2w-1=0 | | 137-(6x+4)=6(x+7)+x | | 12-v=1 | | 16x+2y=32 | | 6(x-2)+4=4(x-6) | | x^4-18x^2+81=0 | | 26x-7-13x+4=26x-9-13x+17 | | -4(2x+8)=2(k+9) | | -12=8z+12 |